Racismo, xenofobia y conflicto individual - Blesa Matienzo, Maria Dolores (2000)
We think about racism and xenophobia in terms of recognize the prejudice bases on a real experience or not. The study of attitudes, groups and individuals in our society supposed social qualities and irrational facts.